PERSEPSI DAN UPAYA MASYARAKAT SETEMPAT TERHADAP PERLINDUNGAN ORANGUTAN (PONGO PYGMAEUS) DI SEKITAR TAMAN NASIONAL DANAU SENTARUM (TNDS) DAN TAMAN NASIONAL BETUNG KERIHUN (TNBK) KABUPATEN KAPUAS HULU - Fifilia, Yolanda; Fahrizal, .; Zainal, Sofyan (Universitas Tanjungpura, 2016)
West Kalimantan Province is one of area that being habitat of orangutan, therefore it is very important to involve local society around Danau Sentarum National Park and Betung Kerihun National Park in Kapuas Hulu district in order to provide a good comprehension about orangutan. Besides that, it able to be expected to make grow awareness and action conserve orangutan, in around TNDS and TNBK in which the place to breeding orangutan and conservation area.The purposes in this research was to determined: 1). Perception of Â society local to protect orangutan (Pongo pygmaeus) around Danau Sentarum National Park and Betung Kerihun National Park, 2) society effort to protect orangutan and 3) The relations between the level of knowledge, cosmopolitan, counseling and perception to protect orangutan.The result in this research showed that the perception local society local to protect orangutan around Danau Sentarum National Park and Betung Kerihun National Park tend to be different. Most respondents have perception that lower it was about (56%) to protect orangutan. From the result of the research showed most of respondents have perception that upper it was about (65.5%) in protecting orangutan around Danau Sentarum National Park and Betung Kerihun National Park.The relationship between the level perception of knowledge has moderate correlation with the value 56%, the perception level of cosmopolitan has moderate correlation with the value 46%, the counseling has moderate correlation with the value 59% and level of perception to protect orangutan has close links with the value 65,5% (strong). In concluded that the orangutan can accepted in most society local area. Keywords: Quantitave Research, Danau Sentarum National Park and Betung Kerihun National Park